Postcolonialism and uneven development - San Juan, Epifanio, Jr. (Iloilo City UP Visayas, 1998)
"Postcolonial theory and discourse may be read as a symptom of "third world" diasporic intellectuals claiming a niche in the global production of knowledge. Otherness becomes ftishized, displaced from the political economy of center-periphery relations. Uneven development in all senses serves as the condition of possibility of postcolonial thought. Only the science of historical materialism, based on Marx, Engels and Lenin, can provide a systematic analysis and critique of postmodern trends like postcolonialism and its neoconservative grounding in the neoliberal program of capitalist globalization."
Keywords: Postcolonialism